Structural And Optoelectronic Characterisations Of Zinc Oxide Structures For Antibacterial Activities On Skin Bacteria - Ling, Chuo Ann (2014)

(untitled)
The main objective for this research work is to investigate the structural and optoelectronic properties of zinc oxide (ZnO) structures with their correlation on antibacterial activities against Staphylococcus aureus (S. aureus), Pseudomonas aeruginosa (P. aeruginosa) and Streptococcus pyogenes (S. pyogenes). Two ZnO powder samples, one with rod-like (ZnO-Pharma) and the other with plate-like (ZnO-White) structures, were characterised for their morphological, structural, optical and electrical properties. Objektif utama penyelidikan ini ialah untuk menyiasat sifat struktur dan optoelektronik struktur zink oksida (ZnO) serta perkaitannya dengan aktiviti antibakteria terhadap Staphylococcus aureus (S. aureus), Pseudomonas aeruginosa (P. aeruginosa) dan Streptococcus pyogenes (S. pyogenes). Dua sampel serbuk ZnO, dengan serbuk pertama mempunyai struktur bentuk rod (ZnO-Pharma) manakala serbuk kedua mempunyai bentuk plat (ZnO-White), telah dicirikan dengan sifat morfologi, struktur, optik dan elektrik.